Miliary osteoma cutis of the face: A case report - Saadia Bouraoui; Mona Mlika; Rim Kort; Fayka Cherif; Ahlem Lahmar; Sabeh Mzabi-Regaya (Our Dermatology Online, 2012)
Introduction: Miliary osteoma cutis (OC) of the face is a rare benign extra skeletal bone formation. For our knowledge, only 23 cases have been reported in the English literature. These lesions may be primary or secondary. They cause diagnostic, therapeutic and cosmetic concern especially in women who are usually concerned. Our purpose is to present a case which is completely documented with the clinical, histological and radiological findings. We also report a possible pathogenic theory according to our histologic findings.Case Report: We report a case of a multiple miliary OC of the face in a 45-year-old woman which suffered from gravidarum acne. These lesions were treated by focal surgical treatment. Conclusions: Based on our histological findings, an osteoblastic metaplasia seems to be a possible pathogenic theory. This metaplasia seems to be secondary to a chronic inflammation. Concerning therapeutic procedures, they are non consensual and debated and are based on surgical or medical treatment. More reports are needed in order to assess the therapeutic management of this disease and its inducing factors.